Implementation of the Drill Method in Learning to Read and Write Javanese Script Class V MI Ma'arif NU Banteran - Indirani Rahayu, Annisa; Kusumaningrum, Endah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research was motivated by a response to educators' efforts to implement innovative learning methods, namely the drill method in learning to read and write Javanese script. The drill method is applied to overcome the difficulties experienced by high class MI students in mastering the skills of reading and writing Javanese script. The aim of this research is to describe the implementation process of learning to read and write Javanese script using the drill method at madrasah ibtidaiyah. This research is based on behavioristic learning theory. The method used in this research is a descriptive qualitative field research method. This research uses observation, interviews and documentation in data collection. The research was conducted on students in the VC MI Ma'arif NU Banteran class for the 2023/2024 academic year. To check the validity of the data in this research, source triangulation and technical triangulation were used. The results of the research reveal that the implementation of the drill method in learning to read and write Javanese script is divided into three stages, namely the planning stage including preparation of lesson plans, preparing students before learning, having complete learning facilities and selecting appropriate methods and evaluation techniques; the implementation stage includes preliminary activities in the form of learningapperception; The core activities consist of introducing Javanese script, practicing writing Javanese script repeatedly, reading simple texts, and composing simple sentences using various techniques or strategies, such as opening or closing books, using interesting learning media, group games, and a student pointing system.; closing activities in the form of drawing conclusions about the material; then the evaluation stage includes written tests and oral test.